AGRICULTURAL EXTENSION DURING THE NEW NORMAL ERA - Warnaen, Andi; Nurlaili, Nurlaili; Yastutik, Yastutik; Karunia, Dowi (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Since the outbreak of COVID-19 in 2020, the pandemic has seriously impacted agriculture sectors. Coffee farmers are one of the groups significantly affected by this pandemic. In addition, agricultural extension, as one of the essential instruments in improving farmers' knowledge and skills, faces new challenges in providing services after the pandemic ends. This study examines the condition of agricultural extension after the Covid-19 pandemic in Malang Regency from the aspects of extension planning, extension materials, methods, media, and extension evaluation. The research was conducted in AMSTIRDAM sub-districts of Malang Regency. This research used a quantitative descriptive method. The research respondents were 97 coffee farmers randomly selected from 2622 coffee farmers. Primary data were obtained through observation, questionnaire distribution, and respondent interviews. Secondary data were obtained from the Agricultural Extension Office. The results showed that during the COVID-19 pandemic or the new normal era, agricultural extension officers continued to develop programs together with farmers even though it was done without face-to-face interaction (online). Agricultural extension workers also continue to facilitate the preparation of RDKK. During the COVID-19 pandemic, agricultural extension workers conveyed more information about capital. The extension method and media use an indirect approach and the use of social media. In addition, agricultural extension workers also continue to evaluate the impact of counseling during the pandemic. It can be concluded that agricultural extension workers continue to carry out extension activities for farmers even with various adjustments during the COVID-19 pandemic by implementing strict health protocols, including reducing face-to-face activities.